Sedimentological characterization of earthquake-generated turbidites in fault-proximal glacial lakes: a case study from Jenny Lake, Teton range, Wyoming - Larsen, Darren J.; Blumm, Aria R.; Crump, Sarah E.; Muscott, Amelia P.; Abbott, Mark B.; Hangsterfer, Alexandra; Porcelli, Maya (Frontiers in Earth Science, 2024)
Lakes in seismically active regions preserve valuable sedimentary archives of paleoseismic activity within their catchment and beyond. A series of glacially-excavated lakes positioned directly along the surface trace of the Teton normal fault at the base of the Teton Range, WY, are ideally situated to record past fault activity since their formation ~15,000 years ago. Here, we focus on the sediment fill contained in Jenny Lake (5 km2; ~73 m max depth) located at the bottom of Cascade Canyon, in the central Tetons, where postglacial slip rates are greatest. Past earthquakes that generated slope failures in and around Jenny Lake are expressed stratigraphically as coseismic turbidite deposits. These deposits were previously identified and dated in sub-bottom profiles and in sediment cores taken from multiple locations around the basin. In this study, we focus on the six thickest turbidites (ranging from 6 to 34 cm thick) present in multiple cores recovered from the central depositional basin and analyze them at sub-centimeter resolution for changes in physical, biological, and geochemical parameters, including sediment density, magnetic susceptibility, grain size distributions, organic content, and elemental composition. Results reveal each deposit contains a well-defined, three-component sedimentary sequence composed of a relatively homogenous and thick basal sandy unit with a sharp bottom contact, a similarly thick silt-rich middle unit, and a thin top unit of very fine-grained sediments. The characteristics of these components and their similarity between individual deposits suggest consistent sediment sources and transport pathways during successive earthquake events. Based on our analyses and the unique local geomorphic setting, we create a mechanistic model of coseismic turbidite formation in Jenny Lake, which may provide an improved framework for identifying, characterizing, and correlating earthquake-generated disturbance deposits in other Teton lakes and lakes in similar tectonic-geomorphological settings, for example in the Basin and Range Province, USA or beyond.